Role of microRNA-498 and microRNA-410 in neonatal hypoxic-ischemic encephalopathy - Eman Salah Eldeen Arafat; Hasnaa Hesham Abotaleb; Dina Abdel Razek Midan; Abdel Hamid Abdo Ismail; Zeinab Sabri Abouzouna (Clinical and Experimental Pediatrics)
Background Neonatal asphyxia is the primary cause of hypoxic-ischemic encephalopathy (HIE), a condition characterized by hypoxic and ischemic brain damage. A class of short noncoding RNAs known as microRNAs (miRNAs) have significant regulatory functions, can function as diagnostic and developmental indicators of diseases, and are involved in disease pathophysiology. Purpose To study the role of microRNA-410 and micro RNA-498 in neonatal HIE as well as control and prevention of neonatal encephalopathy. Methods A case-control study was performed of on 30 full-term neonates with proven HIE, and 30 clinically healthy full-term neonates with no evidence of HIE matched for age and sex serving as controls. The expression of microRNA-498 and microRNA-410 were measured using quantitative real-time polymerase chain reaction. Results Levels of miRNA-410 and miRNA-498 were higher in cases versus controls (1.56±6.43 copies/mL vs 0.58±0.60 copies/mL) and (55.63±118.24 copies/mL vs 3.74± 7.09 copies/mL), respectively. Of the cases, 66.7% were discharged cases and 33.3% died. Overall miRNA-410 had a sensitivity of 70%, specificity of 60%, and cutoff point of ≤0.242, whereas miRNA-498 had a sensitivity of 70%, specificity of 66.7%, and cutoff point >1.854. Conclusion These findings suggest that miRNA-498 and miRNA-410 can be auxiliary diagnostic and prognostic tools for neonatal HIE.